SUSTAINABLE LIVELIHOODS FOR WOMEN IN UNORGANISED SECTOR: A STUDY OF HOME BASED WOMAN WORKERS IN DELHI - Neha Rani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Woman empowerment and sustainable development are primarily co-related in one direction, and sustainable development alone can play an indispensable and pivotal role in reducing inequality between man and woman which is enshrined in SDG Goal-5; in the other direction. Empowering women may benefit in reducing poverty SDG Goal-1, contribute to better education for younger generation, over all health, nutrition and nourishment for those who rely on them (SDGs 2, 3 and 4). Equivalently, elimination of all forms of crime against women and girls (Target no. 5.2) are not only a prerequisite element of SDGs 5 but also crucial to enhancing healthy living and over all well-being for individuals of all ages (SDGs 3). The idea 'sustainable livelihoods' has been presented to define the integration of poverty reduction strategies, sustainable development in every direction, participation of all actors and empowerment process into a structure for policy and project analysis and planning. This research delves into the experiences of women in the unorganized sector, shedding light on their unique challenges and opportunities. The unorganized sector, characterized by informal and non-standard work arrangements, plays a significant role in many economies, particularly in developing countries. Within this sector, women form a substantial workforce, often engaging in low-skilled and precarious jobs. The study reveals the working circumstances and experiences of women who are home based worker. It examines how they balance their responsibilities as caregivers, wage workers, and homemakers while underlining the difficult balancing act they must have. However, the study reveals the numerous challenges faced by women in this sector. It highlights on issues such as low wages, limited job security, lack of social security benefits, and vulnerability to exploitation.